Role of global and local strangeness neutrality in an inhomogeneous freeze-out approach to relativistic heavy ion collisions - Zschiesche,D. (2007)
An inhomogeneous decoupling surface of hadrons produced in relativistic heavy-ion collisions may occur, if the expanding hot and dense matter passes through a first order phase transition. We show that due to the non-linear dependence of the particle densities on the temperature and baryon-chemical potential such inhomogeneities should be visible even in the integrated, inclusive abundances. We analyze experimental data from Pb+Pb collisions at CERN-SPS and Au+Au collisions at BNL-RHIC to determine the amplitude of inhomogeneities and the role of local and global strangeness neutrality.